The Effect of Depth Jump and Box Jump Training on Improving the Leg Muscle Power of Long Jump Athletes - Cindy Putri Nathania Chandra; Alen Rismayadi; Ivan Rivan Firdaus (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of depth jump and box jump exercises on improving the leg muscle power of long jump athletes. The research method used is a true experimental design with a two-group pretest-posttest design. The research subjects consisted of ten athletes from the Indonesian University of Education Athletics Club, who were selected using purposive sampling. The instrument used was a Force Platform, which had a validity of 0.70773 and reliability of 0.9186. The training program was conducted over 12 sessions with a frequency of three times per week, covering the pretest, treatment, and posttest stages. Data analysis was performed using normality, homogeneity, and t-tests with a significance level of 0.05 to see the effect of each type of exercise and the differences between them. The results showed that both depth jump and box jump exercises had a significant effect on increasing the leg muscle power of long jump athletes. However, the increase produced by depth jump exercises tended to be greater than that produced by box jump exercises. In conclusion, depth jump training is more effective in increasing leg muscle power than box jump training, so it can be recommended as an optimal plyometric training method for long jump athletes to improve their jumping performance.